Making learning stick : 20 easy and effective techniques for training transfer - Carnes, Barbara (ASTD Press, 2010)
Training professionals know that one of the gold standards of success is getting learning to take--ensuring that much of what is learned in the training room (or online) actually gets applied on the job where it counts. Make Learning Stick is a practical, easy to use resource aimed at helping trainers hit that sweet spot of application. Readers will find a treasure trove of techniques based on author Barbara Carnes' more than 25 years of experience, much of it focusing squarely on getting people to take what they learn away from the training room and apply it on the job. This book includes updated versions of classic techniques paired with new, technology-based training methods.